Earthquakes, Tsunamis and Nuclear Risks 2016
DOI: 10.1007/978-4-431-55822-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Statistical Analysis for Seismotectonic Provinces Using Earthquake, Active Fault, and Crustal Structure Datasets

Abstract: Seismotectonic zonation for seismic hazard assessment of background faults and earthquakes by the Headquarters for Earthquake Research Promotion (HERP [1]) is based on the results of the seismotectonic boundaries of Kakimi et al. [2]. However, several unsolved problems, such as map scale, remain in this approach for better prediction of the magnitude and frequency of blind earthquakes. The aim of this study was to construct a new quantitative and objective seismotectonic province map for the main islands of Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Their results showed to what degree people were aware of the likelihood of danger and vulnerability in their area of residence. The whole of Japan was zoned in [14] using statistical methods and principal component analysis (PCA) based on gravity, earthquake, active fault and seismic parameters, and in [15] risk assessment using an artificial neural network (ANN) was performed, which addressed the lack of accurate validation methods which can be one of the shortcomings of these studies. Using social, environmental and physical metrics, another study performed post-earthquake hazard modeling and studied the health of individuals and the threat of poisonous insects, using a hierarchical analysis process model to weigh the criteria [16].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed to what degree people were aware of the likelihood of danger and vulnerability in their area of residence. The whole of Japan was zoned in [14] using statistical methods and principal component analysis (PCA) based on gravity, earthquake, active fault and seismic parameters, and in [15] risk assessment using an artificial neural network (ANN) was performed, which addressed the lack of accurate validation methods which can be one of the shortcomings of these studies. Using social, environmental and physical metrics, another study performed post-earthquake hazard modeling and studied the health of individuals and the threat of poisonous insects, using a hierarchical analysis process model to weigh the criteria [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nakajima et al (2009) provide an in-depth analysis of the Tokyo region, and provide important data on slab geometry. Otherwise, research on this topic has focused on the seismic potential of different domains (e.g., Triyoso and Shimazaki, 2012), with a multivariate statistical approach adopted by Kumamoto et al (2016) allowing a revision focused on moment magnitude. Ghimire and Kasahara (2009) focus on stress analysis, linking regional stress axes to P-axis orientation during earthquake moment release, but this analysis did not account for fault kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Today, multivariate statistical analyses to study volcanic phenomena are more addressed to sectorial data (Hernández-Antonio et al 2015;Steinhorst et al 2001;Join et al 1997;Anazawa and Yoshida 1994;Velasco-Tapia 2014;Jamieson et al 2015;Buccianti et al 2015). A multivariate statistical approach applied to interdisciplinary datasets is only present in some works (Kumamoto et al 2016, Avery et al 2017, where it is shown how useful this methods can be for the seismic and volcanic risk assessment. Multidimensional analysis allows, in fact, to explore a subspace of the original variables space where independent phenomena can be more easily identified.…”
Section: Introductionmentioning
confidence: 99%